Pengaruh Discovery Learning terhadap Kesadaran Metakognisi dan Hasil Belajar Peserta Didik - Pangestuti, Dini Aji; Marpaung, Rini Rita T.; Hasnunidah, Neni (Assimilation: Indonesian Journal of Biology Education, 2019)
This study was conducted to find out the effect of discovery learning on student’s metacognitive awareness and cognitive learning achievement. The population of this research was all of the 11th grade MS (Mathematics and Science Program) students of Sumberejo 1 Senior High School. The research sample were students of 11th MS-1 and MS-3 class taken by cluster random sampling technique. This study was quasi-experimental with Pretest Post-test Non-Equivalent Control Group Design. In this study, student’s metacognitive awareness was measured by using MAI (Metacognitive Awareness Inventory) and SEMLI-S (Self-Efficacy and Metacognition Learning Inventory—Science). Meanwhile, student’s cognitive learning achievement was measured by using cognitive test. The data were analyzed statistically by independent sample t-test respectively at 5% significance level. The results showed that the discovery learning model significantly influenced student’s metacognitive awareness and cognitive learning achievement with significant value of each were 0,000. Through this research, we found that the discovery learning model significantly influenced student’s metacognitive awareness and cognitive learning achievement rather than discussion method.